2022
DOI: 10.1051/0004-6361/202244237
|View full text |Cite
|
Sign up to set email alerts
|

A Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE)

Abstract: Context. Low-surface-brightness galaxies (LSBs) contribute to a significant fraction of all the galaxies in the Universe. Ultra-diffuse galaxies (UDGs) form a subclass of LSBs that has attracted a lot of attention in recent years (although its definition may vary between studies). Although UDGs are found in large numbers in galaxy clusters, groups, and in the field, their formation and evolution are still very much debated. Aims. Using a comprehensive set of multiwavelength data from the NGVS (optical), VESTIG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 101 publications
(144 reference statements)
2
13
0
2
Order By: Relevance
“…The finding that field UDGs have far fewer GCs than most cluster UDGs is in tension with the hypothesis of Junais & Boselli (2022), that blue UDGs in the outskirts of Virgo were previously field UDGs and are now transitioning to become red cluster UDGs. However, it is still possible that ram-pressure stripping of field UDGs may explain a small fraction of cluster UDGs, for example those at the lowest masses, which are less GC-rich (Figure 3).…”
Section: Could Field Ultra-diffuse Galaxies Represent Thementioning
confidence: 59%
See 2 more Smart Citations
“…The finding that field UDGs have far fewer GCs than most cluster UDGs is in tension with the hypothesis of Junais & Boselli (2022), that blue UDGs in the outskirts of Virgo were previously field UDGs and are now transitioning to become red cluster UDGs. However, it is still possible that ram-pressure stripping of field UDGs may explain a small fraction of cluster UDGs, for example those at the lowest masses, which are less GC-rich (Figure 3).…”
Section: Could Field Ultra-diffuse Galaxies Represent Thementioning
confidence: 59%
“…have been the progenitors of present-day UDGs in clusters and groups (Leisman et al 2017). More recently, Junais & Boselli (2022) argued that some blue UDGs in the outskirts of the Virgo cluster are being ram-pressure stripped and transforming into the red UDGs typically found in cluster environments. Given that blue UDGs in the field seem to make up a significant fraction of all UDGs (e.g., Jones et al 2018;Prole et al 2019), it is worth addressing the question: Were the UDGs found in present-day clusters and groups once similar to the blue, gas-rich UDGs found in the field?…”
Section: Could Field Ultra-diffuse Galaxies Represent Thementioning
confidence: 99%
See 1 more Smart Citation
“…The infall of the NGC 3258 subcluster is likely to have caused ram pressure stripping. There is also clear evidence for ram stripping in Fornax (e.g., Jones et al 1997;Su et al 2017bSu et al , 2017Serra et al 2023) and Virgo (e.g., Forman et al 1979;Boselli et al 2014;Su et al 2019;Junais et al 2022). However, these two clusters may be experiencing different stages of ram pressure stripping compared to Antlia.…”
mentioning
confidence: 99%
“…The denser cluster environment may also play a key role in producing quiescent UDGs. Cluster UDGs may initially form as diffuse galaxies in the same manner as the bluer field UDGs, but have undergone additional quenching by the cluster environment (Penny et al 2011;Jiang et al 2019;Prole et al 2019;Grishin et al 2021;Junais et al 2020). Even within a single galaxy cluster itself, the immediate environment, such as galaxy density, varies and may alter the properties of UDG populations as a function of cluster radius, substructure, and local inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%